Mitochondrial DNA copy number can influence mortality and cardiovascular disease via methylation of nuclear DNA CpGs - Castellani, Christina A.; Longchamps, Ryan J.; Sumpter, Jason A.; Newcomb, Charles E.; Lane, John A.; Grove, Megan L.; Bressler, Jan; Brody, Jennifer A.; Floyd, James S.; Bartz, Traci M.; Taylor, Kent D.; Wang, Penglong; et al. (Genome medicine, 2020)
Background Mitochondrial DNA copy number (mtDNA-CN) has been associated with a variety of aging-related diseases, including all-cause mortality. However, the mechanism by which mtDNA-CN influences disease is not currently understood. One such mechanism may be through regulation of nuclear gene expression via the modification of nuclear DNA (nDNA) methylation. Methods To investigate this hypothesis, we assessed the relationship between mtDNA-CN and nDNA methylation in 2507 African American (AA) and European American (EA) participants from the Atherosclerosis Risk in Communities (ARIC) study. To validate our findings, we assayed an additional 2528 participants from the Cardiovascular Health Study (CHS) ( N = 533) and Framingham Heart Study (FHS) ( N = 1995). We further assessed the effect of experimental modification of mtDNA-CN through knockout of TFAM , a regulator of mtDNA replication, via CRISPR-Cas9. Results Thirty-four independent CpGs were associated with mtDNA-CN at genome-wide significance ( P < 5 × 10 − 8 ). Meta-analysis across all cohorts identified six mtDNA-CN-associated CpGs at genome-wide significance ( P < 5 × 10 − 8 ). Additionally, over half of these CpGs were associated with phenotypes known to be associated with mtDNA-CN, including coronary heart disease, cardiovascular disease, and mortality. Experimental modification of mtDNA-CN demonstrated that modulation of mtDNA-CN results in changes in nDNA methylation and gene expression of specific CpGs and nearby transcripts. Strikingly, the “neuroactive ligand receptor interaction” KEGG pathway was found to be highly overrepresented in the ARIC cohort ( P = 5.24 × 10 − 12 ), as well as the TFAM knockout methylation ( P = 4.41 × 10 − 4 ) and expression ( P = 4.30 × 10 − 4 ) studies. Conclusions These results demonstrate that changes in mtDNA-CN influence nDNA methylation at specific loci and result in differential expression of specific genes that may impact human health and disease via altered cell signaling.